Emendas parlamentares no contexto da pandemia de covid-19 no Brasil - BONFIM, Raul (Câmara dos deputados, 2021)
The aim of this paper is to analyze the role of budgetary amendments proposed by Brazilian parliamentarians to combat Covid-19. The pandemic demanded an unprecedented effort from the federal government in managing resources in fighting the virus, leading to the relocation of budgetary allocations for specific actions. However, was the Brazilian Legislative able to reorient its priorities and reallocate its budgetary amendments for actions to fight the new Coronavirus? To answer this question, all individual and state benches’ amendments approved by the National Congress and paid by the Executive between the March and September 2020 were analyzed. Our results indicate that not only did the legislator reallocate their amendments to the specific actions indicated by the government, but also these resources were one of the pillars of the Ministry of Health’s budgetary execution in the first months of the pandemics in Brazil.